1995
DOI: 10.1007/bf01541577
|View full text |Cite
|
Sign up to set email alerts
|

Homosexuality, type 1: An Xq28 phenomenon

Abstract: Despite the absence of phenotypic manifestations in alternating generations characteristic of X-linked disorders, a thesis is presented that a major type of Kinsey grades 5 and 6 male homosexuality is determined by a gene in the Xq28 region. A total of 133 families in 78 kinshps of male and female homosexual probands, in addition to 116 families (including those of 40 famous homosexuals) from the literature, revealed an unbalanced secondary sex ratio in the maternal generation of male, but not of female, homos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…[18]), Sykes [19] has proposed that male homosexuality might stem from incomplete penetrance of a mitochondrial haplotype selected for its ability to kill males during intrauterine development. Consistent with this hypothesis is the finding that maternal aunts significantly outnumber maternal uncles in both homosexual [20] and transsexual men [21]. Such female bias is not evident in the males' paternal relatives or in the relatives of lesbians and female transsexuals.…”
Section: Glossarymentioning
confidence: 79%
“…[18]), Sykes [19] has proposed that male homosexuality might stem from incomplete penetrance of a mitochondrial haplotype selected for its ability to kill males during intrauterine development. Consistent with this hypothesis is the finding that maternal aunts significantly outnumber maternal uncles in both homosexual [20] and transsexual men [21]. Such female bias is not evident in the males' paternal relatives or in the relatives of lesbians and female transsexuals.…”
Section: Glossarymentioning
confidence: 79%
“…Camperio Ciani, Corna, and Capiluppi (2004) reported that the female maternal relatives (i.e., mothers, grandmothers, aunts) of androphilic men exhibit greater fecundity compared to the female maternal relatives of gynephilic men in an Italian sample (see also Camperio Ciani, Cermelli, & Zanzotto, 2008;Iemmola & Camperio Ciani, 2008). Other studies have reported elevated fecundity for the mothers (King et al, 2005;Rahman et al, 2008), maternal grandmothers (McKnight & Malcolm, 2000) and maternal aunts (Bailey et al, 1999;Rahman et al, 2008;Turner, 1995) of androphilic males relative to their gynephilic counterparts. VanderLaan (2007a, 2007b) reported that the mothers of fa'afafine were significantly more fecund than those of gynephilic men.…”
Section: Discussionmentioning
confidence: 91%
“…There was no difference in mean skewing between controls and mothers of gay men An increased maternal aunt/uncle ratio was found for male-to-female transsexuals (Green and Keverne 2000) and homosexual men (Turner 1995). Since this increased ratio is hypothesized to be caused by male lethality, we analyzed the sister/brother ratio in our sample of mothers with and without extreme skewing of X-inactivation.…”
Section: Resultsmentioning
confidence: 99%
“…Variation in human sexual preference has a substantial genetic component, and a maternal bias to the inheritance pattern in males was found in some (Green and Keverne 2000;Hamer et al 1993;Turner 1995) but not all (Bailey et al 1999) studies. From the earliest work on the genetic basis of sexual orientation, the X chromosome was studied as a possible location for genes influencing this trait.…”
Section: Introductionmentioning
confidence: 99%